Effect of electrode on electrical and ferroelectric behavior of modified BNT lead-free ceramics - Sanjoom R. (2017)
© 2016 Trans Tech Publications, Switzerland. In this research, the effect of electrode type on electrical i.e. dielectric and ferroelectric behavior of 0.94BNT-0.06BT ceramics was studies. The ceramics were prepared by conventional mixed oxide method. The sample exhibited a pure perovskite structure with rhombohedral phase. For dielectric measurement, the ceramics with Ag pasted electrodes exhibited very high dielectric constants and good responding with low frequency than Au sputtered electrode.